The 52-week high, q-theory, and the cross section of stock returns - George, Thomas J.; Hwang, Chuan-Yang; Li, Yuan (Journal of Financial Economics, 2018)
The Hou et al. (2015) q-factor model outperforms other factor models in capturing the price-to-high (PTH, the ratio of current price to 52-week high price) anomaly; that is, high-PTH stocks earn high future returns. PTH's relations with future profitability and future investment growth are both significantly positive, and they mirror PTH's relation with future returns in the cross section and by time horizons. Incorporating the information about future investment growth contained in price level variables (e.g., PTH) helps the q factors to capture better those anomalies rooted in future investment growth. Together, these results suggest that the PTH anomaly is consistent with the investment capital asset pricing model.